Treatment of amoxicillin by O3/Fenton process in a rotating packed bed. (1st March 2015) - Li, Mo; Zeng, Zequan; Li, Yingwen; Arowo, Moses; Chen, Jianfeng; Meng, Hong; Shao, Lei
Abstract: In this study, simulated amoxicillin wastewater was treated by the O3 /Fenton process in a rotating packed bed (RPB) and the results were compared with the Fenton process and the O3 followed by Fenton (O3  + Fenton) process. The chemical oxygen demand (COD) removal rate and the ratio of 5-day biological oxygen demand to chemical oxygen demand (BOD5 /COD) in the O3 /Fenton process were approximately 17% and 26%, respectively, higher than those in the O3  + Fenton process with an initial pH of 3. The COD removal rate of the amoxicillin solution reached maximum at the Fe(II) concentration of 0.6 mM, temperature of 25 °C, rotation speed of 800 rpm and initial pH of 3. The BOD5 /COD of the amoxicillin solution increased from 0 to 0.38 after the solution was treated by the O3 /Fenton process. Analysis of the intermediates indicated that the pathway of amoxicillin degradation in the O3 /Fenton process was similar to that in the O3  + Fenton process. Contrast experiment results showed that amoxicillin degradation was significantly intensified in the RPB. Highlights: We propose amoxicillin degradation by O3 /Fenton process in a rotating packed bed (RPB). The use of the RPB can significantly enhance amoxicillin degradation. The BOD5 /COD of the as-treated amoxicillin solution reached 0.38. The O3 /Fenton process shows advantages over both O3  + Fenton and Fenton processes.